Norepinephrine Modulates Pyramidal Cell Synaptic Properties in the Anterior Piriform Cortex of Mice: Age-Dependent Effects of β-adrenoceptors - Ghosh, Abhinaba; Purchase, Nicole C.; Chen, Xihua; Yuan, Qi (Frontiers in Cellular Neuroscience, 2015)
Early odor preference learning in rodents occurs within a sensitive period (≤postnatal day (P)10-12), during which pups show a heightened ability to form an odor preference when a novel odor is paired with a tactile stimulation (e.g. stroking). Norepinephrine (NE) release from the locus coeruleus during stroking mediates this learning. However, in older pups, stroking loses its ability to induce learning. The cellular and circuitry mechanisms underpinning the sensitive period for odor preference learning is not well understood. We first established the sensitive period learning model in mice - odor paired with stroking induced odor preference in P8 but not P14 mice. This learning was dependent on NE-β-adrenoceptors as it was prevented by propranolol injection prior to training. We then tested whether there are developmental changes in pyramidal cell excitability and NE responsiveness in the anterior piriform cortex (aPC) in mouse pups. Although significant differences of pyramidal cell intrinsic properties were found in two age groups (P8-11 and P14+), NE at two concentrations (0.1 and 10 μM) did not alter intrinsic properties in either group. In contrast, in P8-11 pups, NE at 0.1 μM presynaptically decreased miniature IPSC and increased miniature EPSC frequencies. These effects were reversed with a higher dose of NE (10 μM), suggesting involvement of different adrenoceptor subtypes. In P14+ pups, NE at higher doses (1 and 10 μM) acted both pre- and postsynaptically to promote inhibition. These results suggest that enhanced synaptic excitation and reduced inhibition by NE in the aPC network may underlie the sensitive period.